An integrated ecological, genetic and geological assessment of long-distance dispersal by invertebrates on kelp rafts - Jonathan M. Waters; Tania M. King; Ceridwen I. Fraser; Dave Craw (Frontiers of Biogeography)
Long-distance dispersal (LDD) is thought to be a key driver of biogeographic processes, yet few direct natural observations have been made of this process. Several studies have characterised diverse benthic epibiotic communities associated with buoyant macroalgae and have proposed that kelp rafting may be an important LDD mechanism for such coastal species. We test for LDD by combining biological, genetic, and geological data from rafted bull-kelp (Durvillaea antarctica) specimens collected in southern New Zealand following a March 2018 storm. Genetic and ecological data strongly indicate that three of 29 detached kelp specimens sequenced (and their associated live epifaunal taxa) had rafted from the sub-Antarctic to mainland New Zealand, traversing both oceanographic and phylogeographic barriers, over the course of an approximately 4-week journey. Numerous additional epifaunal taxa were detected from rafts that had geologically-distant mainland origins. The successful trans-oceanic rafting documented for sub-Antarctic brooding sea-star, chiton and sea-slug taxa presents a mechanism for their broad but phylogeographically disjunct Southern Hemisphere distributions. Moreover, the detection of several such LDD events over the last decade suggests that such journeys are very common over evolutionary timeframes. Although geological and genetic data were informative over different scales, we detected no conflict between the inferences from these distinct data sets, a finding that reinforces the value of integrative approaches to marine biogeography.